SPIFFI observations of the starburst SMMJ14011+0252: Already old, fat, and rich by z = 2.565 - Tecza, M; Baker, A; Davies, R; Genzel, R; Lehnert, MD; Eisenhauer, F; Lutz, D; Nesvadba, N; Seitz, S; Tacconi, L; Thatte, N; Abuter, R; et al. (Institute of Physics Publishing, 2004)
Using the SPectrometer for Infrared Faint Field Imaging (SPIFFI) on the ESO VLT, we have obtained J, H, and K band integral field spectroscopy of the z = 2.565 luminous submillimeter galaxy SMMJ14011+0252. A global spectrum reveals the brighter of this spatially resolved system's two components as an intense starburst that is remarkably old, massive, and metal-rich for the early epoch at which it is observed. We see a strong Balmer break implying a > 100 Myr timescale for continuous star formation, as well as nebular emission line ratios implying a supersolar oxygen abundance on large spatial scales. Overall, the system is rapidly converting a large baryonic mass into stars over the course of only a few hundred Myr. Our study thus adds new arguments to the growing evidence that submillimeter galaxies are more massive than Lyman break galaxies, and more numerous at high redshift than predicted by current semi-analytic models of galaxy evolution.